Performing Romaniness: The Romen Theatre and Its Role in Romani Identity-Construction in 1920s and 30s Soviet Union - Dunajeva, Jekatyerina (Romano džaniben, 2019)
Review article about:- Lemon, Alaina. 2000. Between two Fires: Gypsy Performanceand Romani Memory from Pushkin to Postsocialism. Durham:Duke University Press, 320 s.- O´Keeffe, Brigid. 2013. New Soviet Gypsies: Nationality,Performance, and Selfhood in the Early Soviet Union. Toronto:University of Toronto Press, 328 s.